Early childhood development and nutritional status in urban Ethiopia - Tefera Darge Delbiso; Yakob Desalegn Nigatu; Natan Tilahun (Wiley, 2024)
Abstract Early childhood development (ECD) is crucial for better health and well‐being throughout life, but few studies have examined how ECD relates to child malnutrition. This is mainly due to lack of reliable and disaggregated data on ECD. We estimated the prevalence of ECD delays (communication, fine motor, gross motor, problem‐solving and personal-social) and examined how different ECD domains were associated with child nutritional status in urban Ethiopia. Using a community‐based cross‐sectional survey design, 627 mother-child (12-36 months old) pairs were included in the study. The ECD was assessed using the Age and Stage Questionnaire (ASQ‐3), and the nutritional status was assessed using anthropometric measurements. The association between the ECD domains and nutritional status was analysed using ordinal logistic regression, adjusting for confounding variables. Delays in ECD domains were common, especially in fine motor domain (41.9%); and more than half of the children were stunted (52.8%). Stunting and underweight were associated with ECD delays, while wasting was not. Accordingly, stunted children were more likely to have worst ECD delays in fine motor (odds ratios [OR] = 1.54; 95% confidence interval [CI]: 1.11; 2.15), gross motor (OR = 1.47; 95% CI: 1.05; 2.04) and problem‐solving (OR = 1.41; 95% CI: 1.02; 1.96) domains compared to non‐stunted children. Similarly, underweight children were more likely to have worse ECD delays in gross motor (OR = 1.91; 95% CI: 1.20; 3.04) and fine motor (OR = 1.90; 95% CI: 1.15; 3.15) domains compared to normal children. Coordinated and targeted ECD interventions, such as nurturing care, should be promoted and implemented widely to improve ECD outcomes and child nutrition.